Great Java web programming. - Turner, James (O'Reilly Media, 2009)
"Great Java Web Programming: Level 1 will lay the foundation for getting started creating web applications with a Java backend. Once you've finished the course you'll have all the tools you need to create powerful web applications that are easy to understand and maintain. Even beyond the basics, you'll learn how to leverage advanced language features such as the Java Standard Tag Library to make your applications clean and streamlined, but also secure and fast."--Resource description page.